Measurement of toothed helical gears and worm gears on coordinate-measuring machine - E. V. Nikolaeva; M. Yu. Nikolaev; A. S. Molodtsov; N. E. Pimneva; M. V. Kazakov (Омский научный вестник)
A new method of measuring parts of complex geometric shape on the coordinate measuring machine KIM-1000 of the Russian company «Lapik» has been developed and implemented. The new method allows to determine the basic parameters of helical gears, wheels and worm gear pairs with high accuracy up to 1 µm. Control and measurement of parts is possible not only with a screw, but also with a threaded and intermittent surface. The obtained experimental method of measurement on the coordinatemeasuring machine allows to exclude all the variety of lowproductive hand tools and equipment, improve accuracy and efficiency. And the introduction of automatic measurement on the coordinate measuring machine allows to exclude a number of subjective errors of the operator.